THE RISE OF SMART CITIES – RESULT OF GLOBAL PROBLEMS OR TECHNOLOGY CHALLENGE? - Kopáčková, Hana; Líbalová, Petra (Žilinská univerzita, 2017)
Urban areas are confronted with the problem of high concentration of people with implications for the sustainability, quality of life, and competitiveness of the region. A United Nations (UN) study points out that, for the first time in history, more than half of the population on the planet (54.6 percent or 3.6 billion people) lives in cities. As a consequence of globalization, cities have to solve more problems, public funds need to be better targeted and natural resources need to be explored consciously and responsibly. Digital revolution brought possibility to use technology as a driver to solve old problems by new ways. Moreover, it also brought new options how to enhance sustainable development. Smart City initiatives can be viewed as an innovation as it align new technologies with new processes, new participatory policy, and new management methods. In sum, Smart City represents changes in governance and daily life. In our article we conceptualize Smart City as socio-technical system with focus on the social part. We use traditional socio-technical model, proposed by Leavitt in 1965. We also consider approaches to evaluation of the success of Smart Cities initiatives with possible metrics. As the result we propose evaluation framework for the evaluation of success of Smart City initiatives.
Chytrá města - důsledek globálních problémů, nebo technologických možností?
Keywords: smart city; technology; socio-technical system; evaluation; smart city; chytrá města; technologie; socio-technický systém; hodnocení